Shoulder Periprosthetic Joint Infection and All-Cause Mortality: A Worrisome Association. Issue 1 (23rd January 2022) - Austin, Daniel C.; Townsley, Sarah H.; Rogers, Thomas H.; Barlow, Jonathan D.; Morrey, Mark E.; Sperling, John W.; Sanchez-Sotelo, Joaquin
Abstract : Background: Periprosthetic joint infection (PJI) can be a devastating complication following shoulder arthroplasty. PJI following hip and knee arthroplasties has been found to increase mortality. However, anatomical and bacteriologic differences could potentially result in a different trend after shoulder arthroplasties. Thus, the purpose of the present study was to determine whether there is an association between shoulder PJI and all-cause mortality. Methods: Our institutional Total Joint Registry Database was queried to identify patients who underwent revision shoulder arthroplasty procedures between 2000 and 2018. A total of 1, 160 procedures were then classified as either septic (21.8%) or aseptic (78.2%). Septic revisions were further subdivided into (1) debridement, antibiotics, irrigation, and implant retention (9.1%); (2) 2-stage reimplantation for deep infection (61.3%); (3) implant resection without reimplantation (3.6%); and (4) unexpected positive cultures at revision surgery (26.1%). The most common bacterium isolated was Cutibacterium acnes (64.4%). All-cause patient mortality was determined with use of our registry and confirmed with use of a nationwide mortality database. All-cause crude and adjusted mortality rates were then compared between groups. Results: The 1-year crude mortality rate was 1.8% (95% confidence interval [CI], 0.9% to 2.6%) for the aseptic group and 2.8% (95% CI, 0.7% to 4.8%) for the septic group (p = 0.31). Multivariate Cox regression analysis demonstrated an elevated but statistically similar adjusted hazard ratio for 1-year all-cause mortality of 1.9 (95% CI, 0.8 to 4.6) when comparing the septic to the aseptic group (p = 0.17). The risk of 2-year all-cause mortality was significantly higher in the septic group, with a hazard ratio of 2.2 (95% CI, 1.1 to 4.5; p = 0.029). In univariate analyses, increased 5-year mortality in the septic revision group was associated with age, Charlson Comorbidity Index, and methicillin-resistant Staphylococcus aureus infection, whereas C. acnes infection was associated with lower mortality. Conclusions: Shoulder PJI is associated with an adjusted 2-year all-cause mortality rate that is double that of aseptic patients. The results of the present study should be utilized to appropriately counsel patients who are considered to be at risk for infection following shoulder arthroplasty. Level of Evidence: Prognostic Level III . See Instructions for Authors for a complete description of levels of evidence.